Eco-friendly energy processes and technologies for achieving sustainable development - Danish, Mir Sayed Shah 1987-; Senjyu, Tomonobu 1963- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book identifies sustainability pillars such as environmental, technical, social, institutional, and economic disciplines and explores the longevity of these disciplines through a resource-oriented approach" - Provided by publisher
Keywords: Renewable energy sources; Sustainable agriculture; Sustainable development